Rubeosis faciei diabeticorum is not associated with oxidative stress and skin autofluorescence - Aleksejs Zavorins; Alise Silova; Julija Voicehovska; Janis Kisis (Sociedade Brasileira de Dermatologia, 2019)
Abstract Background Rubeosis faciei diabeticorum is a persistent facial erythema in patients with diabetes mellitus. The actual pathogenesis has not been studied. However, it is speculated to be a cutaneous diabetic microangiopathy. Objective Examine the correlation between the severity of facial erythema and the possible causes of microvascular diabetic complications, namely oxidative stress, hyperglycemia, and cutaneous accumulation of advanced glycation end-products . Methods Patients diagnosed with Type 2 diabetes mellitus (n = 32) were enrolled in the study. The facial erythema index was measured using the Mexameter MX18; cutaneous accumulation of advanced glycation end-products was estimated by measuring skin auto fluorescence with the AGE Reader (DiagnOptics Technologies B.V. - Groningen, Netherlands). Glycated haemoglobin, total antioxidant status, and malondialdehyde were measured in blood by TBARS assay. The correlation between the selected variables was assessed by Spearman's rank test; p ≤ 0.05 was considered statistically significant. Results There was a statistically significant correlation between total antioxidant status and the facial erythema index (ρ = 0.398, p = 0.024). Malondialdehyde, skin autofluorescence, glycated haemoglobin, body mass index, duration of diabetes, and age did not demonstrate statistically significant correlation with the facial erythema index. Study limitations This is an observational study. Elevation of total antioxidant status could have been caused by several factors that might have also influenced the development of rubeosis faciei, including hyperbilirubinemia and hyperuricemia. Conclusions The results contradicted expectations. Total antioxidant status correlated positively with facial erythema index; however, there was no correlation with oxidative stress and skin autofluorescence. Further investigations should be conducted to reveal the cause of total antioxidant status elevation in patients with rubeosis faciei.